Alcohol Risk Environments, Vulnerability, and Social Inequalities in Alcohol Consumption. Issue 5 (3rd September 2018) - Shortt, Niamh K.; Rind, Esther; Pearce, Jamie; Mitchell, Richard; Curtis, Sarah
Abstract : Alcohol and alcohol-related harm are key public health challenges. Research has shown that individual-level factors, such as age and sex, are important predictors of alcohol consumption, but such factors provide only a partial account of the drivers of consumption. In this article, we argue that individual-level factors interact with features of the risk environment to increase the vulnerability of individuals to such environments. Features of the alcohol risk environment include the density of alcohol premises in a neighborhood. Previous research has shown that neighborhoods with a higher density of alcohol outlets have higher levels of both alcohol consumption and alcohol-related harm. There has, however, been a distinct lack of attention paid to the differential ways in which particular sociodemographic groups might be more vulnerable to such risk environments. In this article, we address the risk environment through a primary focus on the local supply and availability of alcohol products (captured using a measure of outlet density) and the relationship with the harmful use of alcohol. Using responses to the Scottish Health Survey (2008–2011), we explore vulnerability through the interaction between individual-level socioeconomic position, measured using household income, and environmental risk to assess differential social vulnerability to such environments. We report findings showing that those in the lowest income groups might be disproportionately affected by outlet density. This evidence suggests that risk environments might not affect us all equally and that there could be socially differentiated vulnerability to such environments.